An Inquiry into of the Use of Narrative in Educational Leadership; A Tool for Finding Motive and Morality in Autobiographical and Instructional Works - Bishop, Claire (2017)
It is said that there are only four different genres: tragedy, comedy, romance and irony (Frye, 1957 quoted in Bruner, 1996: 95). So to which category does the growing body of narrative accounts written by educational leaders belong? For many, being a leader in education can mean isolation as well as tremendous pressure (Stern, 2009) and so where do current educational leaders turn for guidance in how to best fulfil their roles? In the current educational climate there is the expectation that educational leaders will be able to ‘turn around’ a school, or that the results of a school will continue to improve over time. Understandably, educational leaders may look outside of themselves for inspiration and guidance from those who have been successful. In a situation where educational leaders are under a great deal of pressure, have limited time and do not necessarily have the opportunity to seek guidance from those within their sphere of acquaintance, they can turn to literature for help. As technology and the means through which we can access written material is developing, educational leaders and teachers can access mainstream publications from sites such as Amazon in seconds and receive their books the next day. For many educational leaders who are not undertaking qualifications at universities, accessing books through mediums such as Amazon is easier, cheaper and quicker than exploring peer review publications. It is easier to search Twitter for guidance than it is to trawl through books in a library. This has the potential to create a concerning state of affairs for the education system, as it is possible that educational leaders are seeking guidance from sources that are ineffective, poorly researched, misleading, or not suitable for their context. Using the popular online shop Amazon, I have collected a sample of authors whose books are aimed at teachers and educational leaders. The authors of these pieces are extraordinary. Extraordinary in that they hold the esteem of enough people to make it possible for them to be published and special because they have acted or succeed within the educational profession long enough to 5 see themselves and be perceived as examples for others to follow. In the same way that Bruner reminds us, ‘history never simply happens: it is constructed by historians’ (1996:91), our understanding of what good educational leadership consists of is constructed by educational leaders who have this level of gravitas within the education system. The aim of this research is to explore the narrative process, how memory and experience can act as instructional tools in the current educational system. Through this piece of research, I aim to explore questions surrounding the use of these texts and the impact they can have on educational leadership in the United Kingdom. What do these texts reveal when they are read through the lenses of narrative analysis? How are instructions or guidance imparted by authors through the texts read by educational leaders? What consideration have authors taken when writing for their audience? Are there morality issues that need to be taken into consideration when reading these texts? Bruner (1996) argues that are two kinds of narrative: instructional and storytelling. However, my hypothesis is that there is more to this than a dichotomy, that storytelling, in fact, is instructional in nature within the education system in the United Kingdom. With the books that I am exploring in this dissertation, there appears to be an overlap, a subtlety about where instruction begins and storytelling ends; it is important to determine how storytelling is used by educational leaders as well as whether this is an intentional action used in both written and verbal form. Important also, is the understanding of the process through which the story is created by the author, written, read by the reader and then interpreted by them, potentially then being applied to their own educational practice consciously, for example changing a behaviour policy, or unconsciously, such as having a predetermined view of teachers. As Squire et al. tell us: ‘the creation of the story as a co-construction of the narrator, the audiences of the media in which the story appears is characteristic of all narratives.’ For instance, 6 ‘written narratives are shaped by the writer or writers, and their actual, intended or imagined audiences, but also by writers’ and audiences’ levels of literacy, and by the medium of writing itself: what it provides, in terms of complexity, and the possibility of rereading and remaking meanings, and what it leaves out, for example, paralinguistic speech features such as laugher and sighs (Squire, Davis, Esin, Andrews, Harrison, Hyden and Hyden, 2014; 25). It is for this reason that an exploration of these pieces is essential, as their motives are interpreted and reinterpreted at different points. The process through which these texts go through is one that makes them an important area of study within the fields of educational research and narrative. Firstly, these books are written by an educational leader who has been identified by actors such as OFSTED, the Department for Education, educational publishing houses and so on, as an exemplary individual. They then reflect on their life’s work as a teacher and an educational leader, identifying and interpreting events that retrospectively seem important in their journey. These are then communicated from memory into written form. The purpose of these books may vary: some are overtly instructional, some are memoirs and some are an intentional amalgamation of the two. They are then published and sold to their readers, who in turn read them and draw their own interpretations from the text. These interpretations are they either discarded, adapted or applied without change to a new educational setting by the reader. The focus of this dissertation is to explore this process and identify ways in which the interpretation of these texts can impact the practice and decision making of current educational leaders. By understanding this process in greater depth, my aim is to be able to critically evaluate the texts that are used by many teachers and educational leaders to inform their current practice (see fig. 1).